Amino acid modified copper-based metal organic polyhedral with higher peroxidase activity for potassium guaiacol sulfonate detection - Yu Qin; Linlin Chen; Liyan Zheng (Scientific Reports)
Abstract It has been reported some nanozymes could be used as a substitute for natural enzyme to detect H2O2 to some extent. However, the low catalytic effect of these materials limited their further application fields. Hence, to increase the catalytic activity of nanozymes was a hot research topic and many methods have been reported. Among them, surface modification was an important and efficient approach due to the surface of nanomaterials could affect their properties. In this article, three amino acid modified Cu-MOPs: H-Cu-MOP-Glutamine, H-Cu-MOP-Leucine and H-Cu-MOP-Isoleucine were obtained by further coordination interactions of carboxyl group with copper ions. Compared with H-Cu-MOP, the modified Cu-MOP exhibited a higher catalytic activity and a more stable color change, which could broaden its potential application field. Due to its excellent peroxidase activity, H-Cu-MOP-Leucine can be used to detect potassium guaiacol sulfonate with good anti-interference properties. It exhibits a favorable linear range of 5.0 × 10− 5–1.0 × 10− 3 M, and the limit of detection is 1.28 × 10− 5 M, making it suitable for practical applications. The above results indicate that post-modification of MOP can effectively improve its performance, providing a viable strategy for broadening the practical application of MOP in the detection field.